Severe COVID-19 disease is associated with genetic factors affecting plasma ACE2 receptor and CRP concentrations - Verena Vogi; David Haschka; Lukas Forer; Simon Schwendinger; Verena Petzer; Stefan Coassin; Ivan Tancevski; Thomas Sonnweber; Judith Löffler-Ragg; Elisabeth Puchhammer-Stöckl; Marianne Graninger; Dominik Wolf; et al. (Scientific Reports)
Abstract A hyperinflammatory state with highly elevated concentrations of inflammatory biomarkers such as C-reactive protein (CRP) is a characteristic feature of severe coronavirus disease 2019 (COVID-19). To examine a potential role of common genetic factors that may influence COVID-19 outcomes, we investigated whether individuals with a polygenic predisposition for a pro-inflammatory response (in the form of Polygenic Scores) are more likely to develop severe COVID-19. The innovative approach of polygenic scores to investigate genetic factors in COVID-19 severity should provide a comprehensive approach beyond single-gene studies. In our cohort of 156 patients of European ancestry, two overlapping Polygenic Scores (PGS) predicting a genetic predisposition to basal CRP concentrations were significantly different between non-severe and severe COVID-19 cases and were associated with less severe COVID-19 outcomes. Furthermore, specific single nucleotide polymorphisms (SNPs) that contribute to either of the two Polygenic Scores predicting basal CRP levels are associated with different traits that represent risk factors for COVID-19 disease initiation (ACE2 receptor, viral replication) and progression (CRP). We suggest that genetically determined enforced CRP formation may contribute to strengthening of innate immune responses and better initial pathogen control thereby reducing the risk of subsequent hyperinflammation and adverse course of COVID-19.